Apartidarismo ou apolítica (2002-2018): uma análise sobre o comportamento e as atitudes dos eleitores não partidários - Jaeger, Rafaella Lopes Martins (Universidade Federal de São Carlos, 2022)
The main objective of this study is to understand the behavior and attitudes of non-partisan voters. For this analysis, we will seek to understand the behavior in relation to the relevance of this voter's vote to break the pattern of electoral competition dominated by PT and PSDB. And the analysis of attitudes in order to investigate the view of the non-partisan voter who is less educated and who has no interest in politics regarding the vote for Jair Bolsonaro in 2018. The main hypotheses are: the change in the voting pattern affected the break of the PT-PSDB bipartisan pattern and the profile of the apolitical independent is more susceptible to anti-democratic and anti-systemic appeals. In order to confirm or not these answers, the electorate was segmented based on Russell Dalton's Theory of Cognitive Mobilization (2013), which typifies the electorate into four electoral profiles, namely: cognitive partisans, ritual partisans, nonpartisans and independent apolitical, focusing on the last group. This is because, according to Borba, Gimenes and Ribeiro (2015), it would be this segment, formed by low education and low interest in politics, that would represent most Brazilians. The work was divided into three chapters: at first, the theoretical and conceptual construction of the research was presented; then, we discussed the methodological aspects based on data from the Brazilian Electoral Study (ESEB), referring to the 2002, 2014 and 2018 elections; and finally, the results were analyzed in three sections: i) the indices of the variables that make up the theory of cognitive mobilization over the years analyzed; then, ii) the aspects of the vote of voters were indicated based on the typology presented in the highlighted years and, finally, iii) the vote for Jair Bolsonaro among the apolitical independent voter in the 2018 election was investigated more deeply, profile that poses the greatest risk to democracy. It is concluded that the break of the PT-PSDB pattern was not an unexpected rupture, the vote of the non-partisan voter was important for the result of the 2018 election and, therefore, for the victory of Jair Bolsonaro, especially among apolitical independents, thus confirming the main hypotheses of this dissertation. In addition, it was demonstrated that antipetismo had a strong influence on the result among nonpartisans.
Nonpartisanship or apolitical (2002-2018): an analysis of the behavior and attitudes of non-partisan voters
Keywords: Apartidarismo; Apolítica; Voto; Eleições; Comportamento Político; Nonpartisanship; The politics; Vote; Elections; Political Behavior; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO